A high-strength and high-saturation soft magnetic alloy composite material and preparation method thereof
By rapidly cooling and refining the grains of soft magnetic alloy materials and modifying them to form a composite oxide layer on the surface, the balance problem of existing materials between strength and saturation current is solved, and the preparation of high-strength, high-saturation soft magnetic alloy composite materials is achieved.
Patent Information
- Application Number
- CN202310624524.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-30
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-05-30
AI Technical Summary
While maintaining a certain strength, it is difficult for the existing soft magnetic alloy materials to have a high saturation current, and conventional preparation methods lead to low adhesion of oxide films and reduced anti-DC attenuation ability.
By rapidly cooling the grains of refined metal particles, the grain boundary interface is increased to improve the anti-DC attenuation ability. When the surface of the soft magnetic alloy powder is modified, high-speed stirring is used to generate local high temperatures, so that the glass powder is closely attached to form a composite oxide layer, and the bonding strength of the material and anti-DC attenuation ability are improved.
The preparation of high-strength, high-saturation soft magnetic alloy composite materials is realized, which improves the material's anti-DC attenuation ability and application current, and improves the strength and durability of the components.
Smart Images

Figure CN116646140B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of soft magnetic alloy material preparation, and in particular to a high-strength and high-saturation soft magnetic alloy composite material and a preparation method thereof. Background Art
[0002] As the functions of electronic products continue to increase, the power density of the corresponding electronic components is also increasing. At present, the mainstream solution for power supply products is to increase the power by increasing the current. Soft magnetic alloy materials have high resistance to DC attenuation due to their high Bs, and their application is gradually increasing. However, conventional soft magnetic alloy materials mainly form a surface insulation layer by surface coating or relying on the surface oxidation of the material itself to form an oxide film, thereby increasing the resistivity. The thickness of the oxide film is generally around 20nm. The adhesion of this insulating layer is small, resulting in low strength of the manufactured components and easy mechanical damage. In addition, the formation of the oxide film will lead to an increase in the non-magnetic phase, which will lead to a decrease in the material's Bs and a decrease in its resistance to DC attenuation. Therefore, the existing materials cannot have a high saturation current while maintaining a certain strength using conventional preparation methods. Summary of the invention
[0003] In order to solve the problems of the prior art, the first purpose of the present invention is to provide a method for preparing a high-strength and high-saturation soft magnetic alloy composite material. The preparation method of the present invention promotes the refinement of the grains inside the metal particles by rapid cooling during the preparation of the soft magnetic alloy powder, increases the grain boundary interface inside the particles, thereby increasing the material's ability to resist DC attenuation and increasing the applied current, and then during the surface modification of the soft magnetic alloy powder, the local high temperature generated during high-speed stirring is used to make the glass powder more closely attached to the powder, and then the glass powder is further evenly distributed in the oxide generated between the particles through pressure sintering to form a composite oxide layer, thereby improving the bonding strength between the film layer and the magnetic powder, fundamentally improving the bonding force between the particles, and obtaining a more uniform non-magnetic phase to further increase the material's ability to resist DC attenuation. By using this method, a high-strength and high-saturation soft magnetic alloy composite material can be prepared.
[0004] The second object of the present invention is to provide a high-strength and high-saturation soft magnetic alloy composite material prepared by the above preparation method.
[0005] In order to achieve the above object, the present invention adopts the following technical scheme:
[0006] The invention discloses a method for preparing a high-strength and high-saturation soft magnetic alloy composite material. The soft magnetic alloy material is smelted to obtain alloy liquid. After the alloy liquid is sprayed out from a spray plate, it is first cooled in a nitrogen atmosphere and then immediately placed in cooling water for cooling to obtain soft magnetic alloy powder. A coupling agent is used to perform surface modification on the soft magnetic alloy powder to obtain modified powder. The modified powder is mixed with glass powder under stirring to obtain mixed powder. The mixed powder is mixed with resin and then granulated to obtain pellets. The pellets are pressed and molded to obtain magnetic rings. The magnetic rings are sintered to obtain the soft magnetic alloy composite material.
[0007] In a preferred embodiment, the soft magnetic alloy material has the following components, measured by mass percentage: Fe 89.65wt% to 92.92wt%, Si 3.5wt% to 5.0wt%, Cr 3.0wt% to 4.2wt%, C 0.5wt% to 0.8wt%, Mn 0.05wt% to 0.15wt%, P 0.01wt% to 0.05wt%, Al 0.01wt% to 0.05wt%, and B 0.01wt% to 0.10wt%.
[0008] The soft magnetic alloy material of the present invention improves the saturation magnetic flux density of the material through the optimal Fe / Si ratio, and simultaneously suppresses the decrease in magnetic flux density caused by the generation of the non-magnetic FeCr crystal phase by adding elements such as Mn and P, thereby ensuring better saturation performance.
[0009] Preferably, the smelting temperature is 1350-1500°C.
[0010] In a preferred embodiment, the pressure of the nitrogen atmosphere is ≥5 MPa, and the cooling time in the nitrogen atmosphere is ≤2 s.
[0011] The inventors found that the cooling time in a nitrogen atmosphere needs to be controlled. If the cooling time is too long, FeCr crystal phase is easily generated, resulting in deterioration of saturation performance.
[0012] Preferably, the cooling water flow rate is ≥5m 3 / min. The inventor found that the cooling water flow rate needs to be ≥5m 3 / min. If it is too low, the cold-shortage speed will be too low, the grain size inside the particles will grow, the resistivity inside the particles will drop sharply, and the magnetic permeability will deteriorate at high frequencies such as above 1MHz.
[0013] In a preferred embodiment, the particle size of the soft magnetic alloy powder is 6 to 40 μm.
[0014] The inventors have found that when the particle size of the soft magnetic alloy powder is controlled within the above range, the final soft magnetic alloy composite material has the best performance. If the particles are too fine, the powder packing density will decrease after pressing, the non-magnetic air gap will increase and the magnetic permeability will decrease. If the powder is too coarse, the average air gap will decrease and the energy storage capacity of the air gap will decrease, resulting in deterioration of saturation.
[0015] In a preferred embodiment, the coupling agent is selected from at least one of titanate, aluminate and alumino-titanate.
[0016] In actual operation, the soft magnetic alloy powder coupling agent is mixed with the soft magnetic alloy powder in a solvent, and the coupling agent is grafted onto the surface of the soft magnetic alloy powder to obtain the modified powder.
[0017] In a preferred embodiment, the coupling agent is added in an amount of 0.01% to 0.1% of the mass of the soft magnetic alloy powder.
[0018] In a preferred embodiment, the glass powder is selected from SiO2-CaO-Na2O-P2O5-F glass, the particle size of the glass powder is ≤1 μm, and the proportion of SiO2 in the glass powder is ≥65wt%.
[0019] In a preferred embodiment, the modified powder and the glass powder are stirred and mixed at 80° C. to 100° C. at a speed of 1000 to 3000 rpm to obtain a mixed powder.
[0020] The present invention makes the glass powder adhere more tightly to the powder body by using the local high temperature generated by high-speed stirring under the condition of heating. If the rotation speed is too low, the material is easy to agglomerate, which leads to uneven coating and deterioration of the material's magnetic permeability and insulation. Of course, it cannot be too high. If it is too high, the coating layer is easy to wear and fall off, which deteriorates the insulation performance. If the heating temperature is too high, the coupling agent hardens, resulting in deterioration of the grafting property, the insulation layer is easy to fall off, and the insulation performance is reduced. If the temperature is too low, the powder is easy to agglomerate, resulting in uneven coating and deterioration of the material's magnetic permeability and insulation.
[0021] In a preferred embodiment, the resin is a mixed resin consisting of PVB resin and silicone resin, wherein the mass ratio of the resin is PVB resin: silicone resin = 7-9: 1-3.
[0022] The resin of the present invention adopts a mixed resin composed of PVB resin and silicone resin. The silicone resin further fills the silicon oxide remaining in the gaps of the glass powder after high-temperature decomposition, but its film-forming property is poor. By adding a proper amount of PCB to adjust its film-forming property, a bonding layer can be uniformly formed on the surface of the particles. At the same time, PVB is beneficial to the density improvement of the subsequent pressed magnet due to its excellent plasticity. The ratio of PVB resin to silicone resin is controlled within the scope of the present invention, and the final performance is optimal. If PVB is too little, the film-forming property and plasticity of the material are reduced, affecting the density of the magnet and thus causing the deterioration of the magnetic permeability. If PVB is too much, the C content is too high after heat treatment and decomposition, and the insulation of the material is reduced.
[0023] In a preferred embodiment, the resin is added in an amount of 1.0 wt% to 3.0 wt% of the mixed powder.
[0024] Preferably, the pressure of the compression molding is 1500-2000 MPa.
[0025] In a preferred embodiment, the sintering process is to first sinter at normal pressure in an air atmosphere and then sinter under pressure in an air atmosphere; the process of the normal pressure sintering is to first keep the temperature at 120°C to 150°C for 1 to 3 hours and then keep the temperature at 320°C to 360°C for 1 to 4 hours; during the pressure sintering, the pressure in the furnace is maintained at 10MPa to 80MPa before 700°C, and then the temperature is increased to 750°C to 850°C and kept for 0.5h to 1h; during the keeping temperature, the pressure in the furnace is controlled at 3MPa to 10MPa.
[0026] The sintering process of the present invention first adopts normal pressure sintering to allow the volatile substances of PVB and silicone resin to be separated from the magnet after decomposition, and then adopts pressure sintering. Because oxides are gradually generated in the pressure sintering temperature range, pressure is used to promote exchange and penetration between particles, allowing the oxide films between particles to penetrate each other, thereby improving the strength of the magnet.
[0027] The present invention also provides a high-strength and high-saturation soft magnetic alloy composite material prepared by the above preparation method.
[0028] Principles and advantages
[0029] The soft magnetic alloy material provided by the present invention improves the saturation magnetic flux density of the material through the optimal Fe / Si ratio, and at the same time suppresses the generation of the non-magnetic phase FeCr crystal phase by adding elements such as Mn and P, thereby ensuring a better saturation performance. Then, in the process of preparing soft magnetic alloy powder with this soft magnetic alloy material, the grains inside the metal particles are refined by rapid cooling, the grain boundary interface inside the particles is increased, thereby increasing the material's ability to resist direct current attenuation and increasing the applied current. Then, when the surface of the soft magnetic alloy powder is modified, the local high temperature generated during high-speed stirring is used to make (glass) more tightly attached to the powder, and then the glass powder is further evenly distributed in the oxide generated between the particles through pressure sintering to form a composite oxide layer, thereby improving the bonding strength between the film layer and the magnetic powder, fundamentally improving the bonding force between the particles, and obtaining a more uniform non-magnetic phase to further increase the material's ability to resist direct current attenuation. By using this method, a high-strength, high-saturation soft magnetic alloy composite material can be prepared.
[0030] The present invention refines the grains inside the powder and improves the material saturation capacity through ingredient control combined with a powder making process design. Subsequently, the glass micropowder coating and sintering process design is used to reduce the precipitation oxidation of the alloy particles. At the same time, a composite film layer is formed by the glass micropowder and partial oxidation precipitation to enhance the bonding strength between the film layer and the magnetic powder particles, reduce the precipitation oxidation degree, and solve the problem of performance degradation due to oxidation. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 : SEM image of powder of Example 1. It can be seen from the figure that the surface of the powder is evenly covered with a layer of glass-coated powder.
[0032] Figure 2 : SEM image of powder of comparative example 3. It can be seen from the figure that there is no coated powder on the surface of the particles. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present invention will be described clearly and completely below. The described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0034] Embodiment 1:
[0035] An alloy material is selected, and its material composition is 92.92wt% Fe, 3.5wt% Si, 3.0wt% Cr, 0.5wt% C, 0.05wt% Mn, 0.01wt% P, 0.01wt% Al, and 0.01wt% B. The alloy material is placed in a 1350°C melting furnace for smelting, and then the molten steel is sprayed out through a spray plate, and initially cooled in a nitrogen atmosphere, and then quickly dropped into cooling water for cooling to form an alloy powder. The nitrogen pressure is 7MPa, the cooling time in nitrogen is 1.5 seconds, and the flow rate of the cooling water is 5.5m 3 / minute. The particle size distribution of the alloy material powder prepared is in the range of 6μm to 40μm. The alloy powder is surface modified with 0.01% coupling agent, and the powder is dried after completion, and then 0.1wt% glass powder is added to form a mixed powder at 80°C and a stirring speed of 2000rpm, wherein the coupling agent is preferably aluminum titanate, and the glass powder is preferably SiO2-CaO-Na2O-P2O5-F glass. The particle size of the glass powder is preferably 0.8μm. The proportion of SiO2 in the glass powder is 67wt%. PVB and silicone resin are added to the mixed powder to form granulated powder, and pressed into a magnetic ring at a pressure of 2000MPa; the magnetic ring is placed in a kiln and sintered in an air atmosphere to form a final product. In the mixed resin of PVB and silicone resin, the mass ratio of PVB: silicone resin is 7:3, and the mass ratio of the mixed resin to the powder is 3.0wt%. Before sintering, air is preferably introduced before 360°C, and the temperature is kept at 150°C for 3 hours and at 320°C for 4 hours. The magnetic ring is then placed in an air pressure sintering furnace, and the air pressure in the furnace is maintained at 10MPa before 700°C. The maximum sintering temperature is 750°C, and the temperature is kept for 1 hour, with an air pressure of 3MPa.
[0036] Embodiment 2:
[0037] An alloy material is selected, and its material composition is 89.65wt% Fe, 5.0wt% Si, 4.2wt% Cr, 0.8wt% C, 0.15wt% Mn, 0.05wt% P, 0.05wt% Al, and 0.10wt% B. The alloy material is placed in a 1500°C melting furnace for smelting, and then the molten steel is sprayed out through a spray plate, and initially cooled in a nitrogen atmosphere, and then quickly dropped into cooling water for cooling to form an alloy powder. The nitrogen pressure is 7MPa, the cooling time in nitrogen is 1.2 seconds, and the flow rate of the cooling water is 7m 3 / minute. The particle size distribution of the alloy material powder prepared is in the range of 6μm to 40μm. The alloy powder is surface modified with 0.1% coupling agent, and the powder is dried after completion, and then 1.0wt% glass powder is added to form a mixed powder at 100°C and a stirring speed of 1000rpm, wherein the coupling agent is preferably titanate, and the glass powder is preferably SiO2-CaO-Na2O-P2O5-F glass. The particle size of the glass powder is preferably 0.9μm. The proportion of SiO2 in the glass powder is 69wt%. PVB and silicone resin are added to the mixed powder to form granulated powder, and pressed into a magnetic ring at a pressure of 1500MPa; the magnetic ring is placed in a kiln and sintered in an air atmosphere to form a final product. In the mixed resin of PVB and silicone resin, the mass ratio of PVB: silicone resin is 9:1, and the mass ratio of the mixed resin to the powder is 1.0wt%. Before sintering, air is preferably introduced before 320°C, and the temperature is kept at 120°C for 1 hour, and at 360°C for 1 hour. Then, the magnetic ring is put into the air pressure sintering furnace again, and the air pressure in the furnace is kept at 80MPa before 700°C, and the maximum sintering temperature is 850°C. Keep warm for 0.5 hours, and the air pressure is 6MPa.
[0038] Embodiment 3:
[0039] An alloy material is selected, and its material composition is 91.29wt% Fe, 4.5wt% Si, 3.3wt% Cr, 0.7wt% C, 0.10wt% Mn, 0.03wt% P, 0.03wt% Al, and 0.05wt% B. The alloy material is placed in a 1420°C melting furnace for smelting, and then the molten steel is sprayed out through a spray plate, and initially cooled in a nitrogen atmosphere, and then quickly dropped into cooling water for cooling to form an alloy powder. The nitrogen pressure is 6.5MPa, the cooling time in nitrogen is 1.8 seconds, and the flow rate of the cooling water is 5.5m 3 / minute. The particle size distribution of the alloy material powder prepared is in the range of 6μm to 40μm. The alloy powder is surface modified with 0.05% coupling agent, and the powder is dried after completion, and then 0.5wt% glass powder is added to form a mixed powder at a stirring speed of 3000rpm at 90°C, wherein the coupling agent is preferably aluminate, and the glass powder is preferably SiO2-CaO-Na2O-P2O5-F glass. The particle size of the glass powder is preferably 0.6μm. The proportion of SiO2 in the glass powder is 69wt%. PVB and silicone resin are added to the mixed powder to form granulated powder, and pressed into a magnetic ring at a pressure of 1800MPa; the magnetic ring is placed in a kiln and sintered in an air atmosphere to form a final product. In the mixed resin of PVB and silicone resin, the mass ratio of PVB: silicone resin is 8:2, and the mass ratio of the mixed resin to the powder is 2.0wt%. Before sintering, air is preferably introduced before 340°C, and the temperature is kept at 130°C for 2 hours and at 340°C for 2 hours. The magnetic ring is then placed in an air pressure sintering furnace, and the air pressure in the furnace is maintained at 50MPa before 700°C. The maximum sintering temperature is 800°C, and the temperature is kept for 0.8 hours, and the air pressure is 10MPa.
[0040] Comparative Example 1
[0041] The other conditions are the same as those in Example 1, except that the material composition is 90wt% Fe, 5.0wt% Si, 4.2wt% Cr, and 0.8wt% C.
[0042] Comparative Example 2
[0043] The other conditions were the same as those in Example 1, except that the melting temperature was 1300° C. Since the molten steel was viscous and the particle size was too large, the material with the predetermined particle size could not be obtained.
[0044] Comparative Example 3
[0045] The other conditions are the same as those in Example 1, except that the SiO2-CaO-Na2O-P2O5-F glass powder coating is not included.
[0046] Comparative Example 4
[0047] The other conditions were the same as those in Example 1, except that only 3.0 wt % of silicone resin was added during the granulation process.
[0048] Comparative Example 5
[0049] The other conditions are the same as those in Example 1, except that the Si content of the material composition is adjusted to 6.0wt% Si, and the other components are the same, specifically 89.92wt% Fe, 6.0wt% Si, 3.0wt% Cr, 0.5wt% C, 0.05wt% Mn, 0.01wt% P, 0.01wt% Al, and 0.01wt% B.
[0050] Comparative Example 6
[0051] The other conditions are the same as those in Example 1, except that Mn is removed from the material composition, specifically 92.97wt% Fe, 3.5wt% Si, 3.0wt% Cr, 0.5wt% C, 0.01wt% P, 0.01wt% Al, and 0.01wt% B.
[0052] Comparative Example 7
[0053] The other conditions are the same as those in Example 1, except that the particle size of the prepared alloy material powder is within the range of 1 μm to 5 μm.
[0054] Comparative Example 8
[0055] The other conditions were the same as those in Example 1, except that the cooling was performed in nitrogen for 5 seconds.
[0056] Comparative Example 9
[0057] The other conditions are the same as those in Example 1, except that the flow rate of cooling water is 3 m 3 / minute.
[0058] Comparative Example 10
[0059] The other conditions were the same as those in Example 1, except that the stirring speed of the glass composite was 150 rpm.
[0060] The performance of the sintered magnetic rings of the embodiments and comparative examples was evaluated. The number of winding turns N was 13Ts turns. The magnetic permeability μ (1V / 1MHz) and the current point (saturation current) at which the magnetic permeability dropped by 30% of the magnetic ring samples were tested using a 3260B LCR tester. The collapse strength of the magnetic ring was tested using an electronic universal testing machine SH-100. The obtained performance data are shown in Table 1.
[0061] Table 1 Performance comparison of examples and comparative examples
[0062]
[0063] It can be seen from the results of the embodiments and comparative examples that the material strength of the embodiments is significantly higher than that of the comparative example, and the saturation current of the embodiments is also significantly higher than that of the comparative example, which indicates that the material has high saturation current and high strength under the component requirements and process of this patent.
[0064] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as belonging to the patent protection scope of the present invention determined by the submitted claims.
Claims
1. A method for preparing a high-strength and high-saturation soft magnetic alloy composite material, characterized in that: The soft magnetic alloy material is melted to obtain alloy liquid, and after the alloy liquid is sprayed out from the spray plate, it is first cooled in a nitrogen atmosphere, and then immediately placed in cooling water to cool to obtain soft magnetic alloy powder, the soft magnetic alloy powder is surface-modified by a coupling agent to obtain modified powder, the modified powder is mixed with glass powder under stirring to obtain mixed powder, the mixed powder is mixed with resin and granulated to obtain pellets, the pellets are pressed to obtain magnetic rings, and the magnetic rings are sintered to obtain soft magnetic alloy composite materials; The pressure of the nitrogen atmosphere is ≥5MPa, and the cooling time in the nitrogen atmosphere is ≤2s; the flow rate of the cooling water is ≥5m 3 / min; The coupling agent is selected from at least one of titanate, aluminate, and alumino-titanate; The glass powder is selected from SiO2-CaO-Na2O-P2O5-F glass, the particle size of the glass powder is ≤1µm, and the proportion of SiO2 in the glass powder is ≥65wt%; The resin is a mixed resin composed of PVB resin and silicone resin, wherein the mass ratio of the resin is 7-9:1-3. The modified powder and the glass powder are stirred and mixed at 80°C to 100°C and at a speed of 1000 to 3000 rpm to obtain a mixed powder; The sintering process is to first sinter at normal pressure in an air atmosphere, and then sinter at pressure in an air atmosphere; The process of the normal pressure sintering is: first, keep the temperature at 120°C-150°C for 1-3h, then keep the temperature at 320°C-360°C for 1-4h, and during the pressure sintering, keep the pressure in the furnace at 10MPa-80MPa before 700°C, then increase the temperature to 750°C-850°C, keep the pressure in the furnace at 10MPa-80MPa, and keep the temperature for 0.5h-1h; The soft magnetic alloy material has the following components, calculated by mass percentage: Fe 89.65wt%~92.92wt%, Si 3.5wt%~5.0wt%, Cr 3.0wt%~4.2wt%, C 0.5wt%~0.8wt%, Mn 0.05wt%~0.15wt%, P 0.01wt%~0.05wt%, Al 0.01wt%~0.05wt%, and B 0.01wt%~0.10wt%.
2. The method for preparing a high-strength and high-saturation soft magnetic alloy composite material according to claim 1, characterized in that: The smelting temperature is 1350-1500°C.
3. The method for preparing a high-strength and high-saturation soft magnetic alloy composite material according to claim 1, characterized in that: The particle size of the soft magnetic alloy powder is 6-40 μm.
4. The method for preparing a high-strength and high-saturation soft magnetic alloy composite material according to claim 1, characterized in that: The added amount of the coupling agent is 0.01% to 0.1% of the mass of the soft magnetic alloy powder.
5. The method for preparing a high-strength and high-saturation soft magnetic alloy composite material according to claim 1, characterized in that: The added amount of the resin is 1.0wt% to 3.0wt% of the mixed powder mass.
6. The method for preparing a high-strength and high-saturation soft magnetic alloy composite material according to claim 1, characterized in that: The pressure of the pressing molding is 1500~2000MPa.
7. A high-strength and high-saturation soft magnetic alloy composite material prepared by the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
High-permeability and high-saturation magnetically soft alloy material and preparation method thereof
CN113096948A
Dust core and manufacturing method thereof
JP2010027854A